THE INFLUENCE OF PROMOTION STRATEGIES THROUGH SOCIAL MEDIA, ELECTRONIC WORD OF MOUTH, AND BRAND AMBASSADOR ON THE DECISION TO PURCHASE GLAD2GLOW PRODUCTS IN LHOKSEUMAWE CITY - Nadia Nandayani; Hamdiah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of social media promotion strategies, electronic word of mouth (e-WOM), and brand ambassadors on purchasing decisions of Glad2Glow products in Lhokseumawe City. This research is motivated by the rapid development of social media, which influences consumer behavior in making purchasing decisions, particularly in the increasingly competitive skincare industry. The research method used is a quantitative method with an associative approach. The population in this study consists of consumers of Glad2Glow products in Lhokseumawe City, with the sampling technique using purposive sampling. Data were collected through the distribution of questionnaires to respondents who met the criteria. The data analysis technique used is multiple linear regression analysis. The results of the study indicate that social media promotion strategies have a positive and significant effect on purchasing decisions. Electronic word of mouth also has a positive and significant effect on purchasing decisions. In addition, brand ambassadors have a positive and significant influence on purchasing decisions of Glad2Glow products in Lhokseumawe City. Simultaneously, these three variables are able to explain the variation in consumer purchasing decisions. The implications of this study indicate that companies need to optimize digital promotion strategies, improve the quality of consumer reviews on social media, and select appropriate brand ambassadors to enhance purchasing decisions.